The association between weight-adjusted-waist index and cognitive function: the cross-sectional and longitudinal evidence from CHARLS - Qian, Sifan; Wen, Qiuqing; Jiang, Di; Wang, Shiliang; Hu, Xuqiang (Frontiers in Nutrition, 2025)
ObjectiveWeight-adjusted waist index (WWI), a novel indicator of abdominal obesity that reflects body compositional changes due to aging, shows superiority in predicting obesity-related health risks. The present study aimed to investigate the cross-sectional and longitudinal association between WWI and cognitive function in the Chinese middle-aged and older population.MethodsA total of 8,822 individuals were included in cross-sectional analyses, of whom 7,697 had longitudinal data. The baseline WWI was calculated as waist circumference divided by the square root of body weight. Cognitive scores were assessed at baseline and every 2–3 years during follow-up. The primary outcome was cognitive z-scores. Linear regression and generalized estimating equation models were used to assess the cross-sectional association of WWI with cognitive function and its longitudinal association with cognitive decline, respectively.ResultsHigher WWI was associated with lower baseline global cognitive score (β = −0.218 per unit increase; 95% CI: −0.333 to −0.103). Longitudinally, there was a significant association between WWI and accelerated global cognitive decline (β = −0.008 per unit increase; 95% CI: −0.013 to −0.003). However, higher body mass index was associated with slower cognitive decline, whereas waist circumference showed no significant association with cognitive decline.ConclusionHigher baseline WWI levels were independently associated with an increased risk of subsequent cognitive decline, indicating WWI may be a potential obesity indicator for identifying poor cognitive performance among middle-aged and older adults.